Why are urban Indian 6th graders using more tobacco than 8th graders? Findings from Project MYTRI. (24th May 2006) - Stigler, M H; Perry, C L; Arora, M; Reddy, K S
Abstract : Objective: To investigate why urban Indian 6th graders may be using more tobacco than urban Indian 8th graders. Design: Cross-sectional survey of students conducted in the summer of 2004, as the baseline evaluation tool for a group-randomised tobacco prevention intervention trial (Project MYTRI). Mixed-effects regression models were used to (1) examine the relationship between 15 psychosocial risk factors and current use of any tobacco, by grade; and (2) examine differences in psychosocial risk factors, by grade. Setting: Thirty-two private (high socioeconomic status (SES)) and government (low-mid SES) schools in two large cities in India (Delhi and Chennai). Subjects: Students in the 6th and 8th grade in these schools (n = 11642). Among these, 50.6% resided in Delhi ( v Chennai), 61.4% attended a government school ( v a private school), 52.9% were enrolled in 6th grade ( v 8th), and 54.9% were male ( v female). Main outcome measure: Current (past 30 day) use of any tobacco, including chewing tobacco (for example, gutkha), bidis, or cigarettes. Result: Almost all psychosocial factors were significantly related to tobacco use, for students in both grades. Some of the strongest correlates included social susceptibility to and social norms about use. Exposure to tobacco advertising was a strong correlate of tobacco use for 6th graders, but not for 8th graders. Sixth graders scored lower than 8th graders on almost all factors, indicating higher risk. Conclusions: The "risk profile" of 6th graders suggests they would be vulnerable to use and to begin using tobacco, as well as to outside influences that may encourage use.